Expression of a bile acid transporter in biliary epithelial cells from normal and cholestatic rat livers - Elsing, Christoph; Fitscher, Barbara; Böker, Christof; Kramer, Werner; Stengelin, Siegfried; Stremmel, Wolfgang (European journal of medical research, 1999)
A sodium dependent bile acid carrier has recently been cloned and characterized in rat ileum. The present study demonstrates the presence of a mRNA species specific for the rat ileal bile acid carrier (r-IBAT) in rat biliary epithelial cells. Moreover, immunohistochemistry with a peptide specific antibody demonstrates protein expression in biliary epithelial cells from normal and bile duct ligated rat livers. Besides a cytoplasmic staining a predominant staining of the apical membrane could be observed. These observations indicate that biliary epithelial cells are involved in bile acid transport across the biliary tree. In addition the carrier could also play a role in the signal transduction of bile acid induced ductular secretion.